The Poison Frog Mystery #74 - Warner, Gertrude Chandler; Nang Chan Yeema (New York, USA Scholastic Inc., 2000)
The boxcar children are determined to solve the mystery of whoever tries to steal the animals from their local zoo before the zoo loses any more rare animals.
Keywords: Adult Fiction